2009
DOI: 10.1080/09637480802710216
|View full text |Cite
|
Sign up to set email alerts
|

No effect on intake and liking of soup enhanced with mono-sodium glutamate and celery powder among elderly people with olfactory and/or gustatory loss

Abstract: Mono-sodium glutamate (MSG) and/or flavors may improve palatability and intake in elderly people. Whether this improvement is related to a decline in chemosensory sensitivity is unclear. We examined the effect of flavor-enhanced tomato soup (1,200 mg/l MSG (0.12% MSG) + 3 g/l celery powder) versus non-enhanced soup on intake and liking in 120 older adults (72+/-6 years). Olfactory and gustatory performance was measured. For the whole group, no difference in intake (198 g vs. 203 g) (P =0.97), liking (6.6 vs. 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…Knowledge of the decline of taste and olfactory perception with age has led to the use of taste and flavour enhancement of foods, aiming to improve liking and ultimately consumption by older adults. Although this approach has been successful in some studies (2) , it has not in others (3) . In order for such studies to succeed it may be important to know the extent of decline in intensity perception for more complex mixtures of tastants within real food systems, as well as to account for the numerous confounding factors within individual perception.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of the decline of taste and olfactory perception with age has led to the use of taste and flavour enhancement of foods, aiming to improve liking and ultimately consumption by older adults. Although this approach has been successful in some studies (2) , it has not in others (3) . In order for such studies to succeed it may be important to know the extent of decline in intensity perception for more complex mixtures of tastants within real food systems, as well as to account for the numerous confounding factors within individual perception.…”
Section: Resultsmentioning
confidence: 99%
“…Older people frequently complain of blandness of foods or sensory changes that may influence their liking and subsequent consumption of food, further impacting on their risk of malnutrition (1) . Previous researchers have used taste enhancement, aiming to increase liking and consumption of meals by older adults, with conflicting results (2,3) . Therefore, in order to develop foods leading to improved liking and consumption by older adults, analysis of age-related changes in taste perception is essential.…”
mentioning
confidence: 99%
“…Two studies contradict these findings; there was no increase in intake by nursing home residents when food enhanced with flavour and/or MSG (n = 97, age >65) [8], or MSG alone (n = 53, age >65) was consumed [9]. The same group of researchers found no effect from flavour and/or MSG on liking and intake of soup consumed by free living older people (n = 120, age = 72 ± 6) [10]. Potential reasons for differing study results include use of different MSG concentrations, different exposure times and different methods of addition.…”
Section: Introductionmentioning
confidence: 96%
“…Other studies, undertaken in nursing homes and institutions for the elderly, reported a similar dietary intake of foods with and without MSG. However, it should be taken into consideration that the chemosensory perception diminishes with age, and that the heterogeneity of the study population could have masked small differences between the treatment and control group (Essed et al., ; Essed, Kleikers, van Staveren, Kok, & de Graaf, ; Essed, van Staveren, Kok, & de Graaf, ; Rogers & Blundell, ).…”
Section: Clinical Trials On Msg Exposurementioning
confidence: 99%